Asymmetric Regression Models Bernoulli/Log Proportional-Hazard Distribution - Martínez-Flórez, Guillermo; Barrera, Carlos (Revista Colombiana de Estadística, 2014)
In this paper we introduce a kind of asymmetric distribution for nonnegative data called log-proportional hazard distribution (LPHF). This new distribution is used to study an asymmetrical regression model for data with limited responses (censored) through the mixture of a Bernoulli distribution with logit link and the LPHF distribution. Properties of the LPHF distribution are studied, maximum likelihood parameter estimation and information matrices are addressed. An illustration with real data shows that the model is a new alternative for studies with positive data censored.